Chronic airway inflammation provides a unique environment for B cell activation and antibody production. Issue 4 (26th January 2017) - Feldman, S.; Kasjanski, R.; Poposki, J.; Hernandez, D.; Chen, J. N.; Norton, J. E.; Suh, L.; Carter, R. G.; Stevens, W. W.; Peters, A. T.; Kern, R. C.; Conley, D. B.; et al.
Summary: Background: B cells play many roles in health and disease. However, little is known about the mechanisms that drive B cell responses in the airways, especially in humans. Chronic rhinosinusitis (CRS) is an inflammatory disease of the upper airways that affects 10% of Europeans and Americans. A subset of CRS patients develop nasal polyps (NPs), which are characterized by type 2 inflammation, eosinophils and group 2 innate lymphoid cells (ILC2s). We have reported that NP contain elevated levels of B cells and antibodies, making NP an ideal system for studying B cells in the airways. Objective: We sought to determine the mechanisms that drive B cell activation and antibody production during chronic airway inflammation. Methods: We analysed B cells from NP or tonsil, or after ILC2 coculture, by flow cytometry. Antibody production from tissue was measured using Luminex assays and the frequency of antibody‐secreting cells by ELISpot. Formation of B cell clusters was assessed using immunohistochemistry. Expression of genes associated with B cell activation and class switch recombination was measured by qRT‐PCR. Results: NP contained significantly elevated frequencies of plasmablasts, especially those that expressed the extrafollicular marker Epstein–Barr virus‐induced protein 2 (EBI2), but significantly fewer germinal centre (GC) B cells compared with tonsil. Antibody production and the frequency of antibody‐secreting cells were significantly elevated in NP, and there was evidence for local class switch recombination in NP. Finally, ILC2s directly induced EBI2 expression on B cells in vitro . Conclusions and Clinical Relevance: Our data suggest there is a unique B cell activation environment within NP that is distinct from classic GC‐mediated mechanisms. We show for the first time that ILC2s directly induce EBI2 expression on B cells, indicating that ILC2s may play an important role in B cell responses. B cell‐targeted therapies may provide new treatment options for CRSwNP.